Quality Improvement Methodology Optimizes Infliximab Levels in Pediatric Patients with Inflammatory Bowel Disease. Issue 3 (5th May 2021) - Hellmann, Jennifer; Etter, Renee K.; Denson, Lee A.; Minar, Phillip; Hill, Denise; Dykes, Dana M.; Rosen, Michael J.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Achieving and maintaining target serum trough infliximab levels improves outcomes in children and young adults with inflammatory bowel disease. Our goal was to improve adherence to an infliximab therapy guideline. The primary aim was to increase the percentage of patients with infliximab levels ≥5 μg/mL and results checked in the last 12 months from 73% to ≥80% from July 2017 to January 2018. Methods: We participated in Intermediate Improvement Science Series, a course at Cincinnati Children's Hospital Medical Center designed to catalyze change using quality improvement methodology. We implemented interventions through plan-do-study-act cycles. Our outcome measure was balanced by 2 process measures to determine what actions impacted improvement. These measures included the percentage of infusion plans revised in response to a drug level <5 μg/mL and the proportion of plans for which a follow-up drug level was ordered. Results: We increased the percentage of infusion plans revised before the next infusion from 63% to 87% and the percentage of plans that had an appropriate drug level recheck from 61% to 83% from July 2017 to January 2018. We increased the percentage of patients with an infliximab level >5 μg/mL, and results checked in the last 12 months, from 73% to 80%. Conclusions: Quality improvement methodology was effective in improving provider adherence to infliximab therapeutic drug monitoring guidelines. Improvement in adherence to guidelines directly improved the percentage of patients achieving target infliximab levels at any time during infliximab therapy.